Edukasi Pajak: Upaya Menumbuhkan Kesadaran Pajak Sejak Dini Bagi Siswa SMK Negeri 1 Sumenep - Faisol, Moh.; Andriyani; Prasetyo Sasmito, Eko; Helmiyah, Wasilatul; Dyah Eka Putri, Cindy; Rosa Amaliya Putri, Dwi; Siri Nanda, Putri (Universitas Serang Raya, 2025)
The low level of compliance impacts the amount of tax revenue that is not optimal. This results from a low understanding and awareness of taxes and a need for more tax literacy. Tax education activities for SMK Negeri 1 Sumenep students are one way to provide understanding and foster early tax awareness for the younger generation. The method used in this activity consists of four stages: (1) coordination stage, (2) preparation stage, (3) implementation stage, and (4) evaluation stage. Based on the four stages that have been carried out in tax education activities can increase the understanding of taxes owned by students. The increase in understanding is evidenced by the evaluation results of questionnaires filled out by students, who showed differences between before and after participating in the activity. The student's level of understanding before the activity had an average score of 4.52. After the activity, it had an average value of 7.85. It was also proven by the results of statistical tests with the paired sample t-test method with a significance value of 0.000 < 0.05, which stated there was a difference. With the increased understanding gained from this activity, it is hoped that this understanding will grow awareness in fulfilling tax obligations at a productive age later.